Silicon technologies : ion implantation and thermal treatment - Baudrant, Annie (London : Wiley, 2011)
The main purpose of this book is to remind new engineers in silicon foundry, the fundamental physical and chemical rules in major Front end treatments: oxidation, epitaxy, ion implantation and impurities diffusion.
Includes bibliographical references and index.
Keywords: Semiconductor doping; Ion implantation; Semiconductors -- Heat treatment